Analisa faktor penentu penerimaan dan penggunaan aktual mahasiswa terhadap sistem e-Learning - Siska Rahmadani; Agus Salim; Supriadi Panggabean; Dwiza Riana (Universitas Negeri Yogyakarta, 2021)
Sistem pembelajaran online melalui media e-learning merupakan solusi agar kegiatan belajar mengajar tetap terjaga selama pandemi. Agar penerapan dalam penggunaan sistem e-learning berhasil, perlu diperhatikan faktor-faktor yang dapat mempengaruhi penerimaan sistem tersebut. Penelitian ini bertujuan untuk mencari faktor utama yang mempengaruhi penerimaan dan penggunaan aktual sistem e-learning pada mahasiswa. Metode yang digunakan diadopsi dari model Unified Theory of Acceptance and Use of Technology (UTAUT) ditambah variabel baru yaitu course design, course content support, course assessment, dan instructor characteristics. Analisa data menggunakan SmartPLS dengan model PLS-SEM. Dari hasil penelitian course content support, course assessment, dan behavioral intention to use mempunyai pengaruh signifikan terhadap actual use sistem e-learning. Course design, course content support, dan course assessment mempunyai pengaruh signifikan terhadap performance expectancy, dan yang mempunyai pengaruh signifikan terhadap behavioral intention to use dari sistem e-learning adalah performance expectancy dan social influence. Penelitian ini bisa digunakan sebagai bahan referensi bagi perguruan tinggi untuk meningkatkan penerimaan dan penggunaan sistem e-learning.Analysis of determinants of acceptance and actual use of students e-learning systemsAbstractThe online learning system through e-learning media is a solution to maintain teaching and learning activities during the pandemic. In order for the application in the use of e-learning systems to be successful, it is necessary to consider the factors that can affect the system's acceptance. This study aims to find the main factors that influence students' acceptance and actual use of e-learning systems. The method used was adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT) model plus new variables, namely course design, course content support, course assessment, and instructor characteristics. Data analysis using SmartPLS with PLS-SEM model. From the research results, course content support, course assessment, and behavioral intention to use significantly influence the actual use of the e-learning system. Course design, course content support, and course assessment have a significant influence on performance expectancy, and those that have a significant influence on behavioral intention to use the e-learning system are performance expectancy and social influence. This research can be used as reference material for universities to increase the acceptance and use of e-learning systems.